Construction process optimisation - review of methods, tools and applications - Venkrbec, Václav; Galić, Mario; Klanšek, Uroš (HSGI - Croatian Association of Civil Engineers, 2018)
A review of current heuristic techniques and mathematical programming methods is presented in the paper. Modern optimisation modelling tools are presented, common construction optimisation problems are described, and an overview of their recent application is given. It is also stressed that there is ample room for further research on active BIM-based optimisation models, aimed at better management of construction processes. Accelerated development of decision-making models, which combine optimisation methods and information systems, can be clearly predicted for the near future.

A review of current heuristic techniques and mathematical programming methods is presented in the paper. Modern optimisation modelling tools are presented, common construction optimisation problems are described, and an overview of their recent application is given. It is also stressed that there is ample room for further research on active BIM-based optimisation models, aimed at better management of construction processes. Accelerated development of decision-making models, which combine optimisation methods and information systems, can be clearly predicted for the near future.
Construction process optimisation - review of methods, tools and applications
Keywords: BIM; construction production; modelling; optimisation methods; process optimisation; BIM; construction production; modelling; optimisation methods; process optimisation